Cumulative Live Birth Rate and Cost-Effectiveness Analysis of Gonadotropin Releasing Hormone-Antagonist Protocol and Multiple Minimal Ovarian Stimulation in Poor Responders - Liu, Yuan; Su, Rongjia; Wu, Yu (Frontiers in Endocrinology, 2021)
Background: The overall cumulative live birth rate (CLBR) of poor ovarian responders (POR) is extremely low. Minimal ovarian stimulation (MOS) provides a relatively realistic solution for ovarian stimulation in POR. Our study aimed to investigate whether multiple MOS strategies resulted in higher CLBR compared to conventional gonadotropin releasing hormone (GnRH) antagonists in POR. Methods: This retrospective study included 699 patients (1058 cycles) from one center, who fulfilled the Bologna criteria between 2010 and 2018. Overall, 325 women (325 cycles) were treated with one-time conventional GnRH antagonist ovarian stimulation (GnRH-antagonist). Another 374 patients (733 cycles) were treated with multiple MOS including natural cycles. CLBR and time-and-cost-benefit analyses were compared between these two groups of women. Results: GnRH antagonists provided more retrieved oocytes, Meiosis II oocytes, fertilized oocytes, and more viable embryos compared to both the first MOS (p < 0.001) and the cumulative corresponding numbers in multiple MOSs (p < 0.001). For the first in vitro fertilization (IVF) cycle, GnRH antagonists resulted in higher CLBR than MOS (12.92% versus 4.54%, Adjusted OR [odds ratio] 2.606; 95% CI [confidence interval] 1.386, 4.899, p = 0.003). The one-time GnRH-antagonist induced comparable CLBR (12.92% versus 7.92%, Adjusted OR 1.702; 95% CI 0.971, 2.982, p = 0.063), but a shorter time to live birth (9 [8, 10.75] months versus 11 [9, 14] months, p = 0.014) and similar financial expenditure compared to repeated MOS (20838 [17953, 23422] ¥ versus 21261.5 [15892.5, 35140.25] ¥, p = 0.13). Conclusion: Both MOS and GnRH-antagonists provide low chances of live birth in poor responders. The GnRH antagonist protocol is considered a suitable choice for PORs with comparable CLBR, shorter times to live birth, and similar financial expenditure compared to repeated MOS.